Distributed control for smart cranes over mobile network - Lundstedt, Timo (2020)
The aim of this thesis is to research whether it is possible to build a distributed system where automated smart crane works as a part of automated factory ecosystem by utilizing mobile network and edge computing technologies. Future prospects of crane industries from the aspect of the fourth industrial revolution will be reviewed, in which intelligent process components form an ecosystem and improve process efficiency by sharing data over mobile network.